Potential Of Shrimp Meal As A Partial Substituent For Fishmeal In Diets Of Catla Catla(Hamilton)Fingerlings. - Mary Dayana, P J (School of Aquaculture And Biotechonology, KUFOS, 2016)
Abstract- Feeding management plays a critical role in the success of fish culture. The current trend in fish culture is towards increased intensification whereby, provision of feeds becomes necessary and success depends significantly on the availability of well balanced nutritionally complete and cost effective compounded feeds. A global increase in shrimp farming and processing has led to the mass production of shrimp waste. SW comprises of discarded heads, appendages and exoskeletons of prawns, which is partially converted to shrimp meal for use as animal feedstuff. Generally, sundrying or cooking followed by coarse milling are the most common methods of preparing the shrimp meal.